Practices on Zika Virus infection among women attending antenatal care at public clinics in Johor Bahru, Malaysia - Ahmad, Mohd Anwar Shahrir; Md Said, Salmiah; Muhamad Saliluddin, Suhainizam (Community Health Society Malaysia, 2017)
Background: Zika Virus outbreak was announced as Public Health Emergency of International Concern (PHEIC) in February, 2016. This was due to a sudden increase in microcephaly cases and other neurological disorders in some areas affected by the Zika Virus. Studies have also proven that, other than mosquito bites, Zika Virus infection can also be transmitted through sexual intercourse and blood transmission. Johor Bahru saw two confirmed cases of Zika Virus infection, one of which was a pregnant woman. Objectives: To determine the predictors affecting preventive practices on Zika Virus infection among pregnant women attending antenatal check-up at public health facilities in Johor Bahru district in 2017. Methods: A cross sectional study using probability sampling was conducted involving 724 pregnant women in Johor Bahru distric between 15th and 30th of April 2017. Self-administrated questionnaire was used and results were analysed using SPSS version 22.0. Result: The result indicated that majority of the respondents had high level of preventive practices and knowledge related to Zika Virus infection. The predictors used in the study are Muslim, type of house (apartment, flat or condominium), and knowledge showed significant p value (p<0.05). Other variables, including health belief are considered not significant, (p>0.05). Conclusion: Results from this study suggest to create more awareness towards preventive practices techniques on Zika Virus infection, especially towards community living in attached and detached houses. As Zika Virus infection is an emerging disease, with questionable level of knowledge and awareness among Malaysians, more studies should be conducted to narrow the gap.